2016
DOI: 10.1016/j.celrep.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

p53 Activity Results in DNA Replication Fork Processivity

Abstract: p53 induces cell death upon DNA damage, but this may not confer all of its tumor suppressor activity. We report that p53 activation enhances the processivity of DNA replication, as monitored by multi-label fiber assays, whereas removal of p53 reduces fork progression. This is observed in tumor-derived U2OS cells but also in murine embryonic fibroblasts with heterozygous or homozygous p53 deletion and in freshly isolated thymocytes from mice with differential p53 status. Mdm2, a p53-inducible gene product, simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 59 publications
(76 reference statements)
10
97
0
Order By: Relevance
“…The tumor suppressor p53 determines the fate of HDACitreated cells (Mrakovcic et al 2019) and is relevant for DNA replication and HR (Gottifredi and Wiesmüller 2018;Klusmann et al 2016). As we see replication stress/DNA damage in HDACi-treated cells (Fig.…”
Section: Status Of P53 and Its Regulation By Hdaci In Renca Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor suppressor p53 determines the fate of HDACitreated cells (Mrakovcic et al 2019) and is relevant for DNA replication and HR (Gottifredi and Wiesmüller 2018;Klusmann et al 2016). As we see replication stress/DNA damage in HDACi-treated cells (Fig.…”
Section: Status Of P53 and Its Regulation By Hdaci In Renca Cellsmentioning
confidence: 99%
“…Since wild-type p53 is a tumor suppressor (Gottifredi and Wiesmüller 2018;Klusmann et al 2016), its reduction by HDACi raises concerns that such drugs promote chemoresistance. Furthermore, HDACi-induced alterations in EMT factors (Kiweler et al 2018) may promote the mesenchymal phenotype that is linked to chemoresistance (Fischer et al 2015;Zheng et al 2015).…”
Section: Hdac Inhibition Does Not Promote Chemoresistancementioning
confidence: 99%
“…Another potential target is gain of function p53 (GOF p53), a mutant p53 with oncogenic qualities. GOF p53 increases expression of necessary replication proteins and has recently been shown to stabilize replication forks preventing unmanageable levels of stress [108]. …”
Section: Replication Stressmentioning
confidence: 99%
“…It has been shown that MDM2 overexpression inhibits origin firing through activation of the intra S-phase checkpoint, causing unscheduled DNA replication (Frum et al, 2014). Conversely, it has also been shown that p53 activation and subsequent MDM2 upregulation both enhance replication fork progression and increase replication fork processivity (Klusmann et al, 2016). Although these findings appear conflicting, it is tempting to speculate that disruption of the p53/MDM2 axis in human cancers, either by TP53 mutation or MDM2 overexpression, may interfere with origin firing and replication fork stability.…”
Section: Other Oncogenesmentioning
confidence: 99%